2004
DOI: 10.1523/jneurosci.1307-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Stress Causes Heat Shock Protein Induction, Tau Ubiquitination, and the Recruitment of Ubiquitin to Tau-Positive Aggregates in Oligodendrocytes in Culture

Abstract: Molecular chaperones and the ubiquitin-proteasome system are participants in the defense against unfolded proteins and provide an effective protein quality control system that is essential for cellular functions and survival. Ubiquitinated tau-positive inclusion bodies containing the small heat shock protein ␣B-crystallin in oligodendrocytes are consistent features of a variety of neurodegenerative diseases, and defects in the proteasome system might contribute to the aggregation process. Oligodendrocytes, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 56 publications
2
40
0
Order By: Relevance
“…We have validated over-expression of Hsp90 and Dp-1 by western analysis, and results are shown for Hsp90 (Fig 7). The observation of an increased level of a heat shock protein is consistent with recent studies showing that dysregulation of the ubiquitylation and proteasome systems results in induction of several heat shock proteins and accumulation of tau proteins in oligodendrocytes, precursors for myelin synthesizing cells (Goldbaum and Richter-Landsberg, 2004). The increase in CAF-1 may be related to the slow recovery of DNA synthesis after DNA damage to CS cells because this protein interacts with PCNA (Cleaver, 1982).…”
Section: Protein Expression In Cs Cellssupporting
confidence: 87%
“…We have validated over-expression of Hsp90 and Dp-1 by western analysis, and results are shown for Hsp90 (Fig 7). The observation of an increased level of a heat shock protein is consistent with recent studies showing that dysregulation of the ubiquitylation and proteasome systems results in induction of several heat shock proteins and accumulation of tau proteins in oligodendrocytes, precursors for myelin synthesizing cells (Goldbaum and Richter-Landsberg, 2004). The increase in CAF-1 may be related to the slow recovery of DNA synthesis after DNA damage to CS cells because this protein interacts with PCNA (Cleaver, 1982).…”
Section: Protein Expression In Cs Cellssupporting
confidence: 87%
“…The phosphorylation state of tau has been implicated in the degeneration of neurons [101] and linked to mitochondrial dysfunction [102] . Tau has also been shown to be ubiquitinated and to be involved in the cellular distribution of mitochondria in mouse neurons [103,104] .…”
Section: Mitochondrial Involvement With Taumentioning
confidence: 99%
“…The phosphorylation state of tau has been implicated in the degeneration of neurons [101] and linked to mitochondrial dysfunction [102] . Tau has also been shown to be ubiquitinated and to be involved in the cellular distribution of mitochondria in mouse neurons [103,104] .In 2009, a transgenic mouse strain that mimics both Aβ plaque formation and tau tangles was analyzed and it was found that both the plaques and the tangles affected the OXPHOS of the mitochondria [105] . In a more recent work, it has been shown that reduction of the expression of soluble tau is important for the proper distribution of mitochondria in the neurons of rTg4510 mice [104] .…”
mentioning
confidence: 99%
“…HSPs are upregulated as a first line of defense against the accumulation of misfolded proteins, keep unfolded proteins in a competent state to be refolded, and may prevent cell death und maintain the cytoskeleton (Richter-Landsberg and . Proteasomal inhibition leads to HSP induction (Goldbaum and Richter-Landsberg, 2004), and the autophagosomal system can act as a compensatory mechanism when the UPS is impaired (Pandey et al, 2007;Jaenen et al, 2010). Several proteins have been identified, which link the UPS with the autophagic degradation system, including the receptors for ubiquitinated protein aggregates p62/ sequestosome 1 and HDAC6 (histone deacetylase 6).…”
Section: Cellular Stress and Tau Aggregate Formation In Oligodendrocytesmentioning
confidence: 99%